IMPLEMENTASI SUPERVISI OLEH KEPALA SEKOLAH DALAM MENINGKATKAN PROFESIONALISME GURU - Teti Berliani (JMSP (Jurnal Manajemen dan Supervisi Pendidikan), 2017)
Abstract: The purpose of this study is to describe the implementation of the supervision bythe principal in improving the professionalism of teachers in schools that focus on: (1) theimplementation strategy of supervision by the principal in improving the professionalism ofteachers in schools; and (2) the obstacles encountered in the implementation of supervisionby the principal in improving the professionalism of teachers in schools. This study used aqualitative approach with case study design. The results showed first, strategy implementationsupervision by principals in improving the professionalism of teachers in schools include:scheduling carried out regularly in the implementation of supervision; supervision conductedby the principal, vice principal, senior teachers and school supervisors; supervisiontechniques used more emphasis on techniques classroom visits; and the evaluation ofsupervision activities that have been done in order to mutually discuss and exchange ideas oropinions in order to improve the process of teaching and learning in schools. And second, theobstacles encountered in the implementation of supervision by principals indicate that: (1)those aspects of concern to the supervisor in the implementation of supervision at the schoolinclude uniformity in the preparation of lesson plans, availability of teaching, ways andmethods of teaching used by teachers in the teaching and learning process, media conformitylessons with teaching materials are being studied, as well as conditioning active classatmosphere and fun while teaching and learning progress; and (2) the obstacles encounteredin the implementation of supervision by the principal, namely: is the fear that a teacher evenshy away when they wanted to be supervised, teachers’ understanding of the concept ofsupervision it is still very less because there are still some teachers who think that supervisionis rated as the force everything that is desired by the supervisor of the teachers, the provisionof follow-up of the school principal it is still not maximized because the workload reasonprincipals outside school hours, as well as the lack of principals to provide encouragementand motivation for teachers especially in preparing teachers to be supervised.Keywords: supervision, teacher professionalismAbstrak: Tujuan penelitian ini adalah untuk mendeskripsikan tentang implementasi supervisioleh kepala sekolah dalam meningkatkan profesionalisme guru di sekolah yang berfokus pada:(1) strategi implementasi supervisi oleh kepala sekolah dalam meningkatkan profesionalismeguru di sekolah; dan (2) kendala yang dihadapi dalam implementasi supervisi oleh kepalasekolah dalam meningkatkan profesionalisme guru di sekolah. Penelitian ini menggunakanpendekatan kualitatif dengan rancangan studi kasus. Hasil penelitian menunjukkan pertama,strategi implementasi supervisi oleh kepala sekolah dalam meningkatkan profesionalismeguru di sekolah meliputi: penjadwalan yang dilakukan secara teratur dalam pelaksanaansupervisi; supervisi dilaksanakan oleh kepala sekolah, wakil kepala sekolah, guru-guru seniordan pengawas bidang studi di sekolah; teknik supervisi yang digunakan lebih menekankanpada teknik kunjungan kelas; dan adanya evaluasi terhadap kegiatan supervisi yang telahdilakukan guna saling berdiskusi dan bertukar pikiran atau pendapat dalam rangka perbaikanterhadap proses belajar mengajar di sekolah. Dan kedua, kendala yang dihadapi dalamimplementasi supervisi oleh kepala sekolah menunjukkan bahwa: (1) aspek-aspek yangmenjadi perhatian supervisor dalam pelaksanaan supervisi di sekolah meliputi keseragamandalam penyusunan rencana pembelajaran, ketersediaan perangkat mengajar, cara dan metodemengajar yang digunakan guru dalam kegiatan pembelajaran, kesesuaian media pelajarandengan materi ajar yang sedang dipelajari, serta pengkondisian suasana kelas yang aktif danmenyenangkan saat kegiatan pembelajaran berlangsung; serta (2) kendala yang dihadapi dalam pengimplementasian supervisi oleh kepala sekolah, yakni: masih adanya rasa takutyang dimiliki oleh guru bahkan menghindar ketika hendak disupervisi, pemahaman gurumengenai konsep supervisi dirasa masih sangat kurang karena masih ada sebagian guruyang beranggapan bahwa supervisi dinilai sebagai kegiatan memaksa segala sesuatu yangdikehendaki oleh supervisor terhadap guru, pemberian tindak lanjut dari kepala sekolahdirasa masih belum maksimal karena alasan kesibukan kepala sekolah di luar jam sekolah,serta kurangnya kepala sekolah dalam memberikan semangat dan motivasi bagi guru-guruterlebih dalam mempersiapkan diri guru untuk disupervisi.Kata kunci: supervisi, profesionalisme guru DOI: https://doi.org/10.17977/um025v1i32017p218